(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is devoted to the study of synactic relations of words in Uzbek and English languages. It contributes to acquire some information about the concepts of part of speech in language, the syntactical-semantic functions and features of speech units, methods and their specificity, the relations of language and speech, and these relations are explicated samples.